1988
DOI: 10.1002/jcu.1870160604
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in the detection of cervical incompetency

Abstract: In 80 pregnancies with clinical and ultrasonic signs of cervical incompetency, the length of the cervix and the thickness of the anterior wall of a lower uterine segment have been evaluated ultrasonically. We have also measured the width of the endocervical canal and studied the prolapse of fetal membranes (with fetal parts) into the endocervical canal. We evaluated these same parameters in 80 healthy pregnancies. The length of the cervix, the thickness of the anterior wall of a lower uterine segment, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 14 publications
(4 reference statements)
1
22
0
2
Order By: Relevance
“…The present study has demonstrated that the mean cervical length of 37 mm was similar to that of other studies that measured cervical length at 20-24 weeks in low-risk populations in different settings (Table 6) (2,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 88%
“…The present study has demonstrated that the mean cervical length of 37 mm was similar to that of other studies that measured cervical length at 20-24 weeks in low-risk populations in different settings (Table 6) (2,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 88%
“…4351 Andersen et al, in 1990, published a seminal observation in which 113 patients were evaluated with digital examination of the cervix, as well as transabdominal and transvaginal sonographically-determined cervical length. 52 Cervical length determined by transvaginal (but not transabdominal) ultrasound was predictive of preterm delivery.…”
Section: Cervical Length and The Risk Of Preterm Deliverymentioning
confidence: 99%
“…Cervical assessment can also be carried out by transabdominal and transperineal sonography and these alternative routes may be more acceptable to some women. However, transabdominal sonography fails to visualize the cervix in a high proportion of cases and in particular those with a short cervix [3][4][5][6] . Furthermore, successful visualization by transabdominal sonography requires a full bladder which falsely increases cervical length.…”
Section: Introductionmentioning
confidence: 99%